1990
DOI: 10.1128/mmbr.54.1.52-65.1990
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupler-resistant mutants of bacteria.

Abstract: be shown to have unaltered susceptibility to the effect of the uncouplers upon the AjjH'+, are of considerable bioenergetic interest. At least at first blush, their retention of bioenergetic work capacity at submaximal values of the AILH+ appears to represent a departure from the chemiosmotic formulation. In that formulation, the steady-state level of bioenergetic work, represented by, for example, the phosphorylation potential, AG,, is in direct and complete equilibrium with the AlUH+, and the AGpl/AiH+ ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Mitchell (16) used the action of compounds such as dinitrophenol as evidence for the chemiosmotic model of energy coupling, and since this time the action of uncouplers has been studied in some detail (12). Uncouplers are highly lipid-soluble weak acids or bases, and these compounds act in a cyclic fashion to translocate either H+ or OHacross the cell membrane (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell (16) used the action of compounds such as dinitrophenol as evidence for the chemiosmotic model of energy coupling, and since this time the action of uncouplers has been studied in some detail (12). Uncouplers are highly lipid-soluble weak acids or bases, and these compounds act in a cyclic fashion to translocate either H+ or OHacross the cell membrane (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the fields of food microbiology and bacteriology have revealed that microorganisms are extremely inventive in overcoming the threat of chemical agents. Adaptations range from altered cell envelope composition to active transport systems for removal of toxic compounds from the cell (42,137,171,178,217,250). In addition to modifications that are directly related to the threat presented by lipophilic compounds, changes in the protein profile of cells treated with solvents have been observed (2,29).…”
Section: Adaptations To Lipophilic Compoundsmentioning
confidence: 99%
“…In the ab- sence of metabolic activity, the values for the intra-and extracellular pH would be equalized and this would eliminate the ⌬pH component of the proton motive force (Baronofsky et al, 1984;Chen and Bailey, 1993). However, for viable cells where energy is available, the cell will activate its homeostatic mechanism so as to maintain a constant cytoplasmic pH (Booth and Kroll, 1983;Krulwich et al, 1990). Since homeostasis is an energy consuming process that contributes to the overall maintenance energy requirements m e (Padan et al, 1976), the parent strain would consume a larger portion of its available energy for maintenance purposes.…”
Section: Discussionmentioning
confidence: 99%